(untitled) (Research, Society and Development, 2025)
Inclusive Education has been a prominent topic in recent years, as has Rural Education. Even with the Legal Frameworks, the process of inclusion of Rural Education students is still far from this reality. The study aimed to gather information on the current panorama of inclusion in the rural education interface. The methodological path was outlined through a systematic review of the literature, whose search was conducted in the Google Scholar, Scielo and Capes Periodicals databases with the combination of the terms: “Rural Education” AND “Public Policies” AND “Inclusive Education”. After applying the inclusion criteria, eight articles were summarized, where the results dialogue with the process of inclusion in rural schools. Considering the findings of this study, it is crucial to recognize that the interface between Special Education and Rural Education reveals itself not only as a neglected intersection, but as a fertile field for inclusive practices and critical reflections.